Focus Particles in Information Processing: An Experimental Study on Pragmatic Scales with Spanish incluso - Loureda, Óscar; Cruz, Adriana; Rudka, Martha; Nadal, Laura; Recio, Ines; Borreguero Zuloaga, Margarita (Linguistik Online, 2015)
Focus particles have been one of the spotlights of linguistic research during the last fifty years. They have been studied mainly from a syntactic and semantic perspective, in formal and functional approaches. However, in the last years new insights in this field have been developed through pragmatic and textual approaches. From that perspective, focus particles can be considered as a type of discourse particles, as far as their semantic nature and their pragmatic function are concerned. In this paper, we claim that experiments on text processing may help to support this view: by analyzing eye movements during reading and by testing the effective comprehension of utterances, we can demonstrate the key role of the Spanish scalar additive particle incluso ('even') in the process of information retrieval.